(untitled) (Bulletin KNOB, 2002)
In 2000, during a refurbishment of Nieuwe Rijn 30 in Leiden, a study was made of an unusual little fireplace on the first floor. The first questions were: from what period does the fireplace date and was it originally meant as a fireplace or as a stove. The fireplace consists of two parts. A rectangular mantelpiece, with on top of it a narrow, five-sided chimney breast with remnants of stucco ornamentation. Originally there was a stucco trophy in the broad middle section, of which only the contours are still visible. The rear wall of the fire- place is five-sided and at the top it has an opening for a stove pipe with a twelve-centimetre diameter. The front side is covered with slabs of black Belgian marble. When the fireplace was built is not recorded anywhere, but on the basis of stylistic data and data from the archives a building year around 1795 is plausible. It is also practically certain that it concerns a chimney with fireplace that was later converted into a chimney for a stove. From 1856 to 1862 the front room on the first floor of Nieuwe Rijn 30 was the student room of Simon van Gijn (1836-1922), who rented the room from Mr De Vette. In 1853 Van Gijn enrolled as a student of law in Leiden, which study he completed on 19 December 1862. Van Gijn made three detailed watercolours of his student room on the first floor. The fireplace was in the middle of the wall section. Although some authors write that Van Gijn lived with the widow Swart, this is refuted by the data in the various students’ almanacs of the Leiden student union and the notarial deed in which De Vette is mentioned as the owner of the premises. Van Gijn later established himself as a lawyer in Dordrecht. In 1864 he was admitted as a partner in his father’s bank. He was greatly interested in Dutch history and was an enthusiastic collector of prints. He founded the museum that was named after him. In 2000 there was an exhibition here, where the watercolours were presented. Mrs J. Beijerman-Schols was able to locate them to the correct address. Nieuwe Rijn 30 in Leiden, where the characteristic fireplace of Simon’s student room is still to be found.